Unveiling the Potential Role of Dhurrin in Sorghum During Infection by the Head Smut Pathogen Sporisorium reilianum f. sp. reilianum - Coumba Fall; Seunghyun Lim; Ezekiel Ahn; Sunchung Park; Louis K. Prom; Clint W. Magill (Plants)
The cyanogenic glucoside dhurrin is found in sorghum and has been reported for its role in defense against biotic and abiotic stresses, both involving hydrogen cyanide (HCN) release. The fungus Sporisorium reilianum f. sp. reilianum (SRS) causes sorghum head smut and the infection occurs at the seedling stage, later resulting in panicle loss. Here, the focus was to determine the role of dhurrin in sorghum’s reaction against SRS infection. We investigated the genomic basis of HCN potential (HCNp) variation and its relationship with seedlings’ response to SRS inoculation, along with other sorghum traits, and the expression of dhurrin biosynthetic genes in SRS-inoculated young sorghum. Genome-wide association studies (GWAS) using HCNp scores showed significant single nucleotide polymorphisms (SNPs) on chromosomes harboring the dhurrin biosynthetic and catabolic genes but not in proximity. Significant hits were also detected in or near genes encoding proteins involved in plant defense/resistance against biotic stresses. Correlation analyses showed a strong positive relationship between average HCNp scores and latent period in SRS-inoculated sorghum seedlings. RT-qPCR revealed that the dhurrin biosynthetic genes were upregulated in the leaves of the head smut resistant line BTx635 up to two days after SRS inoculation. Our results suggest the involvement of dhurrin in sorghum’s protection against SRS.